PENGARUH KECERDASAN EMOSIONAL DAN TEKANAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL TANGERANG SELATAN - Syafrina Aulia Hijriyanti; Eti Ariyanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Emotional Intelligence (X₁) and Work Pressure (X₂) on Employee Performance (Y) at the Department of Population and Civil Registration of South Tangerang City. The research method used was a quantitative descriptive approach with an associative method. The population in this study consisted of all employees, with a total sample of 67 respondents determined through questionnaire distribution.The partial test results (t-test) show that the Emotional Intelligence (X₁) variable has a positive and significant effect on Employee Performance, with a t-count of 5.685 > t-table of 1.997 and a significance value of 0.000 < 0.05. The Work Pressure (X₂) variable also has a significant effect on Employee Performance, with a t-count of 3.090 > t-table of 1.997 and a significance value of 0.003 < 0.05. The simultaneous test results (F-test) indicate that Emotional Intelligence and Work Pressure together have a significant effect on Employee Performance, with an F-count of 21.612 > F-table of 3.991 and a significance value of 0.000 < 0.05. The multiple correlation coefficient (R) of 0.635 shows a strong relationship between Emotional Intelligence and Work Pressure with Employee Performance. Meanwhile, the coefficient of determination (Adjusted R²) of 0.384 indicates that 38.4% of the variation in Employee Performance can be explained by both variables, while the remaining 61.6% is influenced by other factors not examined in this study. Thus, improving emotional intelligence and effectively managing work pressure can contribute significantly to enhancing employee performance in public institutions.